Overview of oral hygiene and knowledge of dental and oral health in diabetes mellitus patients at Puskesmas Lampa, Duampanua, Pinrang: Gambaran kebersihan gigi dan mulut serta pengetahuan tentang kesehatan gigi dan mulut pada pasien diabetes melitus di Puskesmas Lampa, Duampanua, Pinrang - Sri Oktawati; Dian Setiawati; Asdar Gani; Mardiana Adam; Hasanuddin Thahir; Arni Irawaty Djais; Raoda Juwita; Ibriana; Agung Friadi (Makassar Dental Journal PDGI Makassar, 2024)
To determine the description of oral hygiene and knowledge level and the relationship between knowledge level and oral hygie-ne with periodontal status of diabetes mellitus (DM) patients at Lampa Health Centre, Duampanua, Pinrang. Samples were de-termined based on inclusion criteria, namely outpatients diagnosed with type 1 or 2 DM aged ≥8 years, and willing to become re-search subjects. At the initial stage, knowledge about the relationship between DM and oral health was measured using a question-naire. The implementation of activities began with DHE using leaflets and banner stands, plaque control using disclosing agents and initial therapy in the form of scaling root planing in people with DM who experience periodontal disease. Oral hygiene status was assessed using OHI-S and periodontal disease status was assessed using Periodontal Diseases Index. The relationship between knowledge level and OHI-S and periodontal status was analysed using Kolmogorof Smirnof test (p<0.05). Patients with poor GDS/GDP scores had poor OHI-S status and poor periodontal status. All study subjects had problems in their supporting tissues, 50% gingivitis and 50% periodontitis. It is concluded that there is a relationship between the level of knowledge with OHI-S status and periodontal status in DM patients at Puskesmas Lampa, Duampanua, Pinrang.